1990
DOI: 10.1192/bjp.156.4.488
|View full text |Cite
|
Sign up to set email alerts
|

Patients Leaving Hospital Without the Knowledge or Permission of Staff–Absconding

Abstract: A series of 100 consecutive psychiatric in-patients who absconded from a psychiatric hospital a total of 231 times over ten months was studied. The reasons given for absconding, duration of absence, and mode of return are described. The legal status and ethnic origins of absconders differed significantly from those of the base hospital population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
57
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(71 citation statements)
references
References 3 publications
11
57
1
2
Order By: Relevance
“…Such events occur, to a greater or lesser extent, across diverse psychiatric populations and settings (Baekeland & Lunwell, 1975;Leff et al, 2000;Smith, 1982;Tomison, 1989). Whatever the setting, inevitably clinicians are left grappling with both the meaning of this decision and how best to prevent its recurrence (Falkowski, Watts, Falkowski, & Dean, 1990). Demographic and clinical factors that may be associated with drop-out are broad ranging, and include diverse issues such as age, gender, diagnosis, treatment history, personality, symptom severity, and life style (Chandrasena, 1987;Pages et al, 1998;Tomison, 1989).…”
Section: Introductionmentioning
confidence: 96%
“…Such events occur, to a greater or lesser extent, across diverse psychiatric populations and settings (Baekeland & Lunwell, 1975;Leff et al, 2000;Smith, 1982;Tomison, 1989). Whatever the setting, inevitably clinicians are left grappling with both the meaning of this decision and how best to prevent its recurrence (Falkowski, Watts, Falkowski, & Dean, 1990). Demographic and clinical factors that may be associated with drop-out are broad ranging, and include diverse issues such as age, gender, diagnosis, treatment history, personality, symptom severity, and life style (Chandrasena, 1987;Pages et al, 1998;Tomison, 1989).…”
Section: Introductionmentioning
confidence: 96%
“…For example, Black women in Hammersmith and Fulham (west London) are reported to have lower compulsory admission rates than White women, whereas in Southwark (southeast London), Black women have higher rates (Bebbington et al, 1991). Falkowski et al (1990) showed that Black people were overrepresented among detained absconders from in-patient units. Although Black people often find services unattractive, it is likely that detained patients are more likely to perceive them as unhelpful (Parkman et al, 1997).…”
Section: Assessment and Admission In General Adult Servicesmentioning
confidence: 99%
“…87 It has been postulated that this may be due to a direct causative effect of locked doors on absconding rates, with a British study finding that 17% of mental health patients described the stigma of being on a locked ward as being an influencing factor in their decision to go absent without leave. 88 This stigma may not only affect absconding rates and deter patients from seeking treatment in locked wards, but it has also been argued that the chronic exposure to the stigma of being in a locked unit could increase the risk of relapse, poor compliance and depression in schizophrenic patients. 89 These data suggest that, somewhat counter-intuitively, the personal freedoms associated with open door wards may in fact prevent patients from absconding.…”
Section: Staff and Patient Opinion On Locked Door Policiesmentioning
confidence: 99%